Van Dijk's Critical Discourse Analysis of The “Dapur Keluarga” Song and Its Relevance To The Corruption, Collusion, and Nepotism Phenomenon in Indonesia - Eri Hermawan; Taufik Nurohman; Wiwi Widiastuti (Epistemik Press, 2022)
In 2020 Feast music group released the Uang Muka album. In the album, one song, Dapur Keluarga, represents the phenomenon of Corruption, Collusion, and Nepotism (KKN) in Indonesia. To analyze the discourse of social criticism in the song Dapur Keluarga, Teun A. Van Dijk's critical discourse analysis model has three analytical frameworks. That is text analysis, social cognition, and social context. Qualitative descriptive is a research method that carefully describes and interprets the data from discourse analysis with existing phenomena and is then used to draw relevance between social criticism discourse and KKN phenomena in Indonesia.Based on the results of research using the method of analysis of critical discourse Teun A. Van Dijk, through text structure, social cognition, and social context analysis, found that the Dapur Keluarga has a meaning with the message of social criticism delivered satirically to human actions in seeking to profit from the suffering of others such as the practice of Corruption, Collusion, and Nepotism carried out by the corrupt and those closest to them (family and relatives) who It is depicted in the Dapur Keluarga. The relevance of discourse is found in the real problems in Indonesia. Cases of KKN practice involving family members and closest people, such as the case of the Regent of East Kutai, Bansos West Bandung, Gratification of Cases in the Supreme Court, and many more. In conclusion, the discourse of social criticism of the lyrics of the Dapur Keluarga song has relevance to the phenomena of Corruption, Collusion, and Nepotism in Indonesia.